Black youth suicide is not new: Early contributions, recent advancements, and remaining gaps in the field - Janelle R. Goodwill (SSM - Mental Health, 2025)
Suicides among Black youth have surged in recent years, with rates of completed suicides for Black children under age 13 being nearly twofold of that for White children of the same age. Attempts among Black teens have also surpassed that of their peers from other race groups. In response to these disheartening trends, federal funding agencies had previously published calls for proposals that directly target matters of suicide prevention among Black youth – a decision that may have led some to believe that suicide is new phenomenon within this population. In this article I argue that while Black youth suicide began to receive more attention in academic, media, and philanthropic outlets, scholars warned of rising suicide rates for Black youth more than three decades earlier. Further, I outline nine areas of priority concern that researchers should consider when working to prevent suicide among Black youth in the future.